J-curve in Turkish bilateral trade: A nonlinear approach. Issue 1 (2nd January 2019) - Ari, Ali; Cergibozan, Raif; Cevik, Emre
ABSTRACT: This study aims to bring further evidence on recent developments of the J-curve literature by employing linear and nonlinear autoregressive distributed lag (ARDL) approaches for Turkish bilateral trade data with respect to 18 European Union member countries over the period from 1990Q1 to 2017Q3. Findings obtained from the nonlinear ARDL model yield more support for the J-curve phenomenon compared to the linear model. This result provides evidence of an asymmetrical impact of appreciations and depreciations on the Turkish bilateral trade balances and suggests that allowing for nonlinearity in the adjustment process gives better results in terms of the J-curve effect.